Manajemen Strategis Pendayagunaan Zakat BAZNAS Jawa Barat terhadap Kesejahteraan Mustahik - Fitriani, Kulsum; Machendrawaty, Nanih; Sadiah, Dewi (Tadbir: Jurnal Manajemen Dakwah, 2022)
This study aims to determine the strategic management of zakat utilization on the welfare of mustahik in BAZNAS, West Java Province. The method used in this research is a descriptive method with a qualitative approach. The results show that environmental observations have been carried out to maximize strengths and take advantage of existing opportunities and minimize weaknesses and threats so that utilization has an impact on the welfare of the mustahik. Strategy Formulation, namely the formulation of a vision, goals, strategies, and policies that are formed systematically. Strategy implementation with five major programs that are made in a mature and professional manner. Evaluation and Control Strategy by conducting regular evaluations so that program control can be carried out properly according to procedures. BAZNAS West Java Province has carried out strategic management well and has been able to show success in the welfare of mustahiq.